Tanggung Jawab Perusahaan Kepada Pekerja Yang Dirumahkan Akibat Pandemi Covid-19 Sebagai Keadaan Memaksa (Force Majeur) : (Studi Di Hotel Jayakarta Lombok) - Anggita Putri Nabilah; Lalu Hadi Adha (Private Law, 2022)
This study aims to determine the implementation of the Jayakarta Hotel Lombok's responsibilities in supporting the fulfilment of the rights and obligations of workers temporarily laid off due to the Covid-19 pandemic and the factors that affect the implementation of their responsibilities. This study uses empirical legal research methods using field data as the main data. The result of the research is that the implementation of the responsibility of Hotel Jayakarta Lombok is to continue to provide wages to permanent workers who are temporarily dismissed, but only 50% of the initial salary and incentives are given in the amount of Rp. 500,000, while contract employees are given 25% of the initial salary and incentives are given in the amount of Rp.300,000. Factors that affect the implementation of the responsibility of Hotel Jayakarta Lombok are juridical and non-juridical factors, juridical factors, namely labour laws and regulations related to presidential decrees and ministerial decisions to governor's circulars, especially in handling laid-off workers due to the Covid-19 pandemic. Meanwhile, what is meant by non-juridical factors refers to everything that is the policy of the Jayakarta Hotel Lombok.